Use of CPAP to Reduce Arterial Stiffness in Moderate-to-Severe Obstructive Sleep Apnoea, Without Excessive Daytime Sleepiness (STIFFSLEEP): an Observational Cohort Study Protocol - Mineiro, A (2016)
INTRODUCTION: Sleepiness is a cardinal symptom in obstructive sleep apnoea (OSA) but most patients have unspecific symptoms. Arterial stiffness, evaluated by pulse wave velocity (PWV), is related to atherosclerosis and cardiovascular (CV) risk. Arterial stiffness was reported to be higher in patients with OSA, improving after treatment with continuous positive airway pressure (CPAP). This study aims to assess whether the same effect occurs in patients with OSA and without sleepiness. METHODS AND ANALYSIS: This observational study assesses the CV effect of CPAP therapy on a cohort of patients with moderate-to-severe OSA; the effect on the subcohorts of sleepy and non-sleepy patients will be compared. A systematic and consecutive sample of patients advised CPAP therapy will be recruited from a single outpatient sleep clinic (Centro Hospitalar de Lisboa Central-CHLC, Portugal). Eligible patients are male, younger than 65 years, with confirmed moderate-to-severe OSA and apnoea-hypopnea index (AHI) above 15/hour. Other sleep disorders, diabetes or any CV disease other than hypertension are exclusion criteria. Clinical evaluation at baseline includes Epworth Sleepiness Scale (ESS), and sleepiness is defined as ESS above 10. OSA will be confirmed by polygraphic study (cardiorespiratory, level 3). Participants are advised to undertake an assessment of carotid-femoral PWV (cf-PWV) and 24 hours evaluation of ambulatory blood pressure monitoring (ABPM), at baseline and after 4 months of CPAP therapy. Compliance and effectiveness of CPAP will be assessed. The main outcome is the variation of cf-PWV over time.